Da Vila do Cariperana à nova territorialização da Comunidade Remanescente Quilombola do América nas narrativas de moradores no contexto bragantino - SILVA FILHO, Claudio Padilha da (Universidade Federal do Pará, 2025)
This thesis analyzes the historical process of the formation of the Quilombola Remnant Community of América (CRQ), in the municipality of Bragança-Pará, in the Para Amazon, motivated by the dispossession of residents of the village of Cariperana, due to differences of opinion, conflicts, interests and the reduction of the area in which they lived and were socially constituted in the work of agriculture and the production of water flour. The two communities are located in the municipality of Bragança, in the northeast of the state of Pará, and are configured in the context of the networks of territorial, socio-spatial, socio-cultural and political-legal meanings established by Brazil's 1988 Federal Constitution. The thesis takes the oral source approach, which assumes that oral discourses can be transformed into written texts that become witnesses (Meihy, Holanda, 2015). Thus, the empirical field research started by listening to the oral narratives of residents (the elders of the two villages), indicating collaborators and the guardians of memory. Methodologically, the thesis is based on the perspective of Social History in studies of history and memory, memory and identity. The historical analysis of the two villages in the constitution of the quilombola community is contextualized despite the origin and relations of the presence of black Africans and their descendants in order to highlight the distinct formation of their historicities. The constitution of a new territorialization based on public policies for racial equality is analyzed, discussing the diasporic movements in search of better living and working conditions in the Pará Amazon by black people and their descendants, which gave rise to the villages of Cariperana and Américo. The theoretical field on processes of territory, deterritorialization and new territorialization are approached from three perspectives: historical -temporal, spatial and symbolic, based on the theory of Haesbaert (2004; 2005). Data was collected using interviews with Afro-descendants who are descendants of the couple Gregório and Tereza, as well as their wife Andreza. Collaborators Júlio Monteiro, Nezila, João Paulo, Orlandina and Manoel Carivaldo took part. The analysis of the interpretative categories regarding the origin of the black population of the two villages was based on the theory of oral history by Thompson (1992), as well as the use of the graphic representation of the 'genogram' symbols to explain the family generations of both villages, indicating the descendants of the collaborators in this research. The results of the thesis point to reflections on the territory and the conflicts between families, the social, economic and cultural relationship in the activity of working with the planting of manioc and the kiln house, highlighting the network of territorial meaning with the certification of quilombola remnant communities in the Amazonian context. The social and cultural role of the presence of women as leaders in the territorial occupation movement, the ethnic-racial recognition of the Quilombola Remnant Community of América based on the implementation of the National Policy for the Sustainable Development of Traditional Peoples and Communities in accordance with Brazil's legal provisions. The thesis concludes that the village of Cariperana and the village of Américo gave rise to the new territorialization of the Quilombola Remnant Community of América, as well as the policies for valuing the history and culture of the African and Afro-Brazilian Continent, which recognized the ancestry of the territory in 2015 and in 2023 was titled.